Numerical Analysis of the Stress-Strain State of Two Unanchored Interacting Circular-Shaped Workings - Tiutkin, O. L.; Demchenko, I. V. (Science and Transport Progress, 2025)
Purpose. The authors aim to perform a numerical analysis of the stress-strain state of two unsupported circularly influenced workings and determine the change in stresses and strains of finite element models depending on the distance between the workings. Methodology. We analyze analytical and numerical approaches to solving the problem of the stress-strain state of two unsupported circularly influenced workings. Within the framework of the analytical approach, two hypotheses of the occurrence of mutual influence based on the theoretical principles of geomechanics, but without a thorough generalization, are considered. In contrast to analytical methods, a more fruitful approach to the problem can be considered the use of numerical methods, in particular the finite element method. Using the professional calculation complex Structure CAD, three finite element models of two unsupported circular workings with a distance between them of one, three, and five diameters were developed. Findings. The analysis of the displacement components and normal stresses along the horizontal and vertical axes for different distances between two unsupported workings ranging from one to five diameters was performed. Moreover, in order to compare the stresses of the considered cases, a single working was also calculated, the stress-strain state of which is considered in this study to be the reference state. It was found that the stress isofields along the horizontal axis at a distance of one diameter (D) between the workings increased by 1.2...1.3 times compared to a single workings, which indicates a clearly expressed mutual influence. Originality. Based on the analysis of the obtained results, the change in stresses and displacements of two unsupported circularly influenced workings for different options of distances between them was estimated. Practical value. Proposals have been developed for the location of two unsupported circular workings in such a way that the influence between them is determined and controlled.